Self-assembled Thy-coated ZIF-8 nanoparticle, self-enhanced multifunctional fresh-keeping composite film and preparation method and application of self-assembled Thy-coated ZIF-8 nanoparticle and self-enhanced multifunctional fresh-keeping composite film
By encapsulating Thy into ZIF-8 nanoparticles and introducing it into the CS-PA matrix, a composite film from enhanced multifunctional fresh-keeping CS-PA/Thy@ZIF-8 was prepared, which solved the problem of existing packaging materials being difficult to extend the shelf life of fruits and environmental pollution, and achieved the dual effects of extended fruit shelf life and environmental protection.
Patent Information
- Application Number
- CN202411469218.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-21
AI Technical Summary
Existing food packaging materials are difficult to effectively extend the shelf life of fruits, and there are problems such as environmental pollution and difficulty in degradation.
A composite film from enhanced multifunctional fresh-keeping CS-PA/Thy@ZIF-8 is prepared by encapsulating thymeol (Thy) into ZIF-8 nanoparticles and introducing it into a chitosan-proanthocyanin (CS-PA) matrix.
This composite film significantly extends the shelf life of the fruit in fruit storage after harvest, has excellent antioxidant properties and continuous antibacterial effects, and has good biodegradability and environmental protection properties.
Smart Images

Figure CN119592085A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional films, and in particular, relates to a self-assembled Thy@ZIF-8 nanoparticle, a self-enhanced multifunctional fresh-keeping composite film, and a preparation method and application thereof. Background Art
[0002] Fresh fruit is essential to a healthy diet and is one of the most popular foods in the world. Unfortunately, more than one-third of fruits rot and spoil before they are eaten each year, causing serious food waste and economic losses. Therefore, it is particularly important to extend the shelf life of fruits. However, the freshness of fruits is affected by many factors, including oxygen, respiration and microorganisms. On the one hand, oxygen and respiration accelerate the oxidation and deterioration, water loss and skin shrinkage of fruits. On the other hand, rich nutrition also promotes the growth and reproduction of microorganisms, thereby aggravating the mildew and decay of fruits. Among the many preservation technologies, food packaging materials play a vital role in preventing food from spoiling and extending the shelf life of food. At present, the most commonly used food preservation packaging materials on the market are mostly polymer plastic packaging cling films, which are usually made of petroleum-based polymers such as polyvinylidene chloride and polyethylene. Although it is cost-effective and easy to use, it has challenges in recycling and degradation, resulting in serious environmental pollution. In recent years, with the development of biotechnology, the transition from traditional fresh-keeping packaging materials to degradable and environmentally friendly packaging materials has become an inevitable trend in the development of modern food packaging. Existing biodegradable green food packaging materials can be mainly divided into biopolymers such as starch, protein, polysaccharide, and lipid, which have excellent properties such as renewable, biodegradable, biocompatible and environmentally friendly. Compared with films prepared from lipids or proteins, polysaccharide-based films are the most attractive due to their excellent gas barrier properties and mechanical properties. Among them, chitosan (CS) is a relatively common natural polymer that has attracted much attention for many years due to its excellent performance. However, due to its linear structure and the presence of a large number of hydrogen bonds, the antioxidant activity of CS films is low and they can only be dissolved in acidic environments, which further limits their application.
[0003] The present invention aims to develop a self-enhanced multifunctional fresh-keeping active packaging material with good antioxidant and antibacterial properties by incorporating active natural compounds into CS films. The material not only has the advantages of inhibiting the growth of pathogenic bacteria and extending the shelf life of fresh food, but also can achieve biodegradation and protect environmental health. Among the many active natural compounds, proanthocyanidins (PA), also known as condensed tannins, are natural bioflavonoids formed by the condensation of flavan-3-ols as a natural antioxidant. They are widely found in fruits, vegetables, seeds and flowers. By grafting PA onto CS films, their solubility and antioxidant properties can be further improved. In addition, thymol (Thy) is also favored by many people for its significant antibacterial and antioxidant properties and good biosafety. However, Thy has poor thermal stability, volatility and water solubility, which limits its biological activity to a certain extent. At the same time, the unique flavor of Thy will also affect the original sensory properties of packaged food. Encapsulating Thy into nanocarriers is one of the effective strategies to solve the above problems. Compared with directly encapsulating Thy into biopolymer matrices, the addition of nanocarriers can better control the release of active substances, thereby providing composite films with more durable antibacterial and antioxidant properties. In terms of nanocarriers, metal organic framework materials (MOFs) represented by ZIF-8 have been widely used in drug delivery and sustained release in biomedicine due to their porous structure, high specific surface area and structural diversity. In addition, ZIF-8 releases unsaturated Zn 2+ Destroying the bacterial structure makes it easier for active materials to enter bacterial cells, achieving synergistic antibacterial effects. Based on this, the present invention prepares Thy@ZIF-8 nanoparticles by encapsulating Thy into ZIF-8 nanoparticles, and simultaneously introduces them into the CS-PA matrix to prepare a self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film, which has excellent antioxidant properties and sustained antibacterial effects in the post-harvest preservation of fruits. Summary of the invention
[0004] In order to solve the problems of difficult degradation, environmental pollution and poor preservation effect of existing traditional food packaging materials, the present invention aims to provide a degradable fresh-keeping film and a preparation method thereof. The film uses a natural polymer, chitosan, as a substrate, natural active compounds, proanthocyanidins and thymol, as encapsulation agents, and a metal organic framework material, ZIF-8, as a nanocarrier. The prepared self-reinforced multifunctional fresh-keeping composite film can be used for the post-harvest preservation of fruits.
[0005] The first object of the present invention is to provide a ZIF-8 loaded Thy nanoparticle and a preparation method thereof, so as to solve the problem that Thy has poor thermal stability, volatility and water solubility in practical applications and its own unique flavor affects the original sensory properties of packaged food. Taking advantage of the high porosity and large specific surface area of ZIF-8 itself, ZIF-8 is used as a carrier to encapsulate Thy to prepare Thy@ZIF-8 nanoparticles.
[0006] Specifically, the first aspect of the present invention provides a self-assembled Thy@ZIF-8 nanoparticle, wherein the self-assembled Thy@ZIF-8 nanoparticle is a nanoparticle formed by encapsulating thymol Thy in a metal organic framework material ZIF-8.
[0007] The second aspect of the present invention provides a method for preparing the self-assembled Thy@ZIF-8 nanoparticles, comprising the following steps:
[0008] 2-Methylimidazole and thymol were dissolved in a first organic solvent and then treated with ultrasound and Zn 2+ The precursor solutions were mixed evenly, stirred for reaction, and then centrifuged to obtain Thy@ZIF-8 nanoparticles.
[0009] The second object of the present invention is to provide a self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film based on Thy@ZIF-8 nanoparticles and a preparation method thereof. By means of the hydrogen bonds formed between the polysaccharide matrix and the components of the nanoparticles, and the hydrogen bonds between the polysaccharide matrix and the Zn 2+ The formed coordination bonds showed excellent compatibility between Thy@ZIF-8 nanoparticles and CS-PA polysaccharide matrix, thus further enhancing the physical properties and antibacterial properties of CS polysaccharide matrix films.
[0010] Specifically, the third aspect of the present invention provides a self-reinforced multifunctional fresh-keeping composite film, wherein the film is based on chitosan, and at least part of the chitosan is grafted with proanthocyanidins, and the film contains the above-mentioned self-assembled Thy@ZIF-8 nanoparticles.
[0011] The fourth aspect of the present invention provides a method for preparing the above-mentioned self-reinforced multifunctional fresh-keeping composite film, comprising the following steps:
[0012] Chitosan-proanthocyanidin conjugate CS-PA and Thy@ZIF-8 nanoparticles were dissolved in distilled water respectively and stirred rapidly at room temperature to obtain CS-PA dispersion and Thy@ZIF-8 dispersion. CS-PA dispersion and Thy@ZIF-8 dispersion were added into chitosan film-forming solution for blending reaction. The blended solution after reaction was film-formed and dried to obtain CS-PA / Thy@ZIF-8 composite film.
[0013] The third object of the present invention is to apply the self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film to the post-harvest preservation of fruits and vegetables (such as strawberries and cherry tomatoes). Through the change of pH in the microenvironment of the fruit during storage, the Thy@ZIF-8 nanoparticles in the composite film release Thy and unsaturated Zn 2+ , combined with the PA released from the CS-PA polysaccharide matrix, the purpose of synergistic antibacterial and antioxidant effects is achieved, thereby extending the shelf life of the fruit.
[0014] Specifically, the fifth aspect of the present invention provides the use of the self-assembled Thy@ZIF-8 nanoparticles or the self-reinforced multifunctional fresh-keeping composite film in the post-harvest storage of fruits and vegetables.
[0015] The technical effects of the present invention are:
[0016] First, the present invention prepares and optimizes self-assembled Thy@ZIF-8 nanoparticles, and for the first time uses them as a material component for preparing post-harvest preservation films for fruits. The active substance Thy is encapsulated by utilizing the porous structure and high specific surface area of ZIF-8 nanoparticles to prepare synthetic Thy@ZIF-8 nanoparticles. Due to the change in the pH of the microenvironment during the storage of fruits after harvest, the structure of Thy@ZIF-8 nanoparticles is destroyed, releasing Thy, achieving the purpose of slow release and prolonging the antibacterial effect. In addition, ZIF-8 itself releases unsaturated Zn 2+ , which can destroy the bacterial structure and make it easier for active molecules to enter the bacterial cells, thus achieving synergistic antibacterial effects.
[0017] Second, the present invention synthesizes a self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film by filling the prepared Thy@ZIF-8 nanoparticles into the CS-PA polysaccharide matrix. The characterization results show that the hydrogen bonds formed between the polysaccharide matrix and the components of the nanoparticles, and the Thy@ZIF-8 2+ The formed coordination bonds significantly improve the physical properties of the composite film, thus achieving self-reinforcement. In addition, the combination of Thy@ZIF-8 nanoparticles and active substances in the CS-PA polysaccharide matrix also achieves synergistic antioxidant and antibacterial effects.
[0018] Third, the self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film of the present invention was tested for its fresh-keeping effect on post-harvest strawberries and cherry tomatoes under actual storage conditions. The experimental results showed that the composite film can significantly extend the shelf life of post-harvest fruits, and there are significant differences in nutritional indicators and sensory evaluation compared with the control group. In addition, no other auxiliary materials are required during the experiment, nor are any large-scale facilities and ultraviolet and irradiation light sources. The fresh-keeping effect is discernible to the naked eye, and the prepared composite film has the advantages of low cost, good biocompatibility, and biodegradability.
[0019] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.
[0021] Figure 1 This is a schematic diagram of the principle of preparing and preserving the composite film of the present invention.
[0022] Figure 2 The encapsulation efficiency of nanoparticles with different Thy addition amounts is shown.
[0023] Figure 3 The PA content of the conjugates with different PA addition amounts is shown.
[0024] Figure 4 The characterization results of ZIF-8 and Thy@ZIF-8 nanoparticles are shown. (a) and (b) are SEM images of ZIF-8 and Thy@ZIF-8, respectively; (c) and (d) are particle size analysis of ZIF-8 and Thy@ZIF-8, respectively; (e) Zeta potential analysis of Thy, ZIF-8 and Thy@ZIF-8; (f) XRD spectra of ZIF-8 and Thy@ZIF-8; (g) FT-IR spectra of Thy, ZIF-8 and Thy@ZIF-8; (h) TG curves of Thy, ZIF-8 and Thy@ZIF-8.
[0025] Figure 5 The characterization results of CS-PA / Thy@ZIF-8 composite films are shown. (a) SEM images of CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film; (b) AFM images; (c) XRD patterns; (d) FT-IR patterns; (e) XPS patterns.
[0026] Figure 6The performance measurement results of CS-PA / Thy@ZIF-8 composite films are shown. (a) Stress-strain curves of CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film; (b) transmittance; (c) water contact angle; (d) cumulative release of Thy under different pH conditions; (e) antioxidant properties.
[0027] Figure 7 The antibacterial ability of CS-PA / Thy@ZIF-8 composite film is shown. (a) and (b) are the growth curves of PE cling film, CS film, CS-PA film, CS-PA / Thy film, CS-PA / Thy@ZIF-8 composite film co-cultured with Staphylococcus aureus and Escherichia coli; (c) bacterial dead / alive staining images after co-culture of different films with Staphylococcus aureus and Escherichia coli; (d) bacterial colony images and SEM images after co-culture of different films with Staphylococcus aureus and Escherichia coli.
[0028] Figure 8 The biocompatibility of CS-PA / Thy@ZIF-8 composite films is shown. (a) Hemolysis rate of sheep red blood cells by CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film; (b) Cell viability of L929 cells after co-culture with different films; (c) Cell viability of L929 cells co-cultured with CS-PA / Thy@ZIF-8 composite films at different concentrations; (d) Degradability of composite films; (e) Peanut sprout growth experiment to evaluate the safety of composite films.
[0029] Fig. 9 The following table shows the (a) appearance, (b) weight, (c) hardness, (d) vitamin C content, (e) TSS content, (f) MDA content, (g) TA content, (h) CAT activity of strawberries after storage in PE cling film, CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film; (i) sensory evaluation of strawberries in different storage groups (second day of storage); and (j) sensory evaluation of strawberries in different storage groups (sixth day of storage).
[0030] Fig.10 The appearance of cherry tomatoes after storage in PE cling film, CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film is shown.
[0031] Fig.11The following table shows the (a) weight loss rate, (b) hardness, (c) vitamin C content, (d) TSS content, (e) TA content, (f) MDA content, (g) total phenolic content, (h) flavonoid content, and (i) CAT activity of cherry tomatoes after storage in PE cling film, CS film, CS-PA film, CS-PA / Thy film, and CS-PA / Thy@ZIF-8 composite film. DETAILED DESCRIPTION
[0032] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0033] The invention provides a self-assembled Thy@ZIF-8 nanoparticle. The self-assembled Thy@ZIF-8 nanoparticle is a nanoparticle formed by encapsulating thymol Thy with a metal organic framework material ZIF-8.
[0034] According to a preferred embodiment of the present invention, the content of ZIF-8 in the self-assembled Thy@ZIF-8 nanoparticles is 70-85% by weight, and the content of Thy is 15-30% by weight.
[0035] The present invention also provides a method for preparing the above self-assembled Thy@ZIF-8 nanoparticles, comprising the following steps:
[0036] 2-Methylimidazole and thymol were dissolved in a first organic solvent and then treated with ultrasound and Zn 2+ The precursor solutions were mixed evenly, stirred for reaction, and then centrifuged to obtain Thy@ZIF-8 nanoparticles.
[0037] According to a preferred embodiment of the present invention, the first organic solvent is anhydrous methanol; the Zn 2+ The precursor is Zn(NO3)2·6H2O; 2-methylimidazole and Zn 2+ The molar ratio of the precursors is 2-12:1; the mass ratio of 2-methylimidazole to thymol is 200-300:1.
[0038] According to a preferred embodiment of the present invention, the stirring reaction conditions include: temperature of 10-30° C., time of 16-36 hours, and washing and vacuum drying steps after the stirring reaction.
[0039] Furthermore, the present invention provides a self-reinforced multifunctional fresh-keeping composite film, wherein the film is based on chitosan, and at least part of the chitosan is grafted with proanthocyanidins, and the film contains the above-mentioned self-assembled Thy@ZIF-8 nanoparticles.
[0040] According to a preferred embodiment of the present invention, the content of self-assembled Thy@ZIF-8 nanoparticles in the self-reinforced multifunctional fresh-keeping composite film is 25-35% by weight; the content of proanthocyanidins is 15-25% by weight.
[0041] The present invention also provides a method for preparing the self-reinforced multifunctional fresh-keeping composite film, comprising the following steps:
[0042] Chitosan-proanthocyanidin conjugate CS-PA and Thy@ZIF-8 nanoparticles were dissolved in distilled water respectively and stirred rapidly at room temperature to obtain CS-PA dispersion and Thy@ZIF-8 dispersion. CS-PA dispersion and Thy@ZIF-8 dispersion were added into chitosan film-forming solution for blending reaction. The blended solution after reaction was film-formed and dried to obtain CS-PA / Thy@ZIF-8 composite film.
[0043] According to a preferred embodiment of the present invention, the preparation method of the chitosan-proanthocyanidin conjugate CS-PA comprises: adding a hydrogen peroxide solution containing ascorbic acid to an acetic acid solution of chitosan, reacting for a period of time, adding proanthocyanidins, reacting at room temperature, adjusting the reaction solution to neutral after the reaction, collecting the precipitate by centrifugation, washing, and freeze-drying to obtain the chitosan-proanthocyanidin conjugate CS-PA.
[0044] The present invention has no particular limitation on the reaction conditions for preparing the composite film, and the reaction can be carried out at room temperature. The reaction time is sufficient as long as the solution is stirred evenly without particles. The same effect can be achieved by appropriately changing the stirring time and rotation speed.
[0045] According to a preferred embodiment of the present invention, the method for preparing the chitosan film-forming solution comprises: dissolving chitosan in glacial acetic acid to prepare a chitosan solution, and adding glycerol as a plasticizer to obtain the chitosan film-forming solution.
[0046] The film-making method is as follows: pouring the blended solution onto a plastic plate.
[0047] The self-assembled Thy@ZIF-8 nanoparticles or the self-enhanced multifunctional fresh-keeping composite film of the present invention can be used for post-harvest storage of fruits and vegetables. As an example, the present invention tests the fresh-keeping effect of the enhanced multifunctional fresh-keeping composite film on strawberries and cherry tomatoes, but its application is obviously not limited to these two fruits.
[0048] The present invention is further illustrated by the following examples.
[0049] If the specific conditions are not specified in the examples, all the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, all of them are conventional products that can be purchased from the market.
[0050] Preparation Example 1
[0051] (1) Synthesis of ZIF-8 self-assembly material: 2.4 g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 6.9 g 2-methylimidazole (2-methylimidazole) were dissolved in 30 mL anhydrous methanol. The mixture was stirred gently for 2 h at room temperature. The zinc nitrate methanol solution was slowly added to the 2-methylimidazole methanol solution while stirring. After 24 h of reaction, a white suspension was obtained. The white precipitate was collected by centrifugation at 9000 rpm / min for 5 min, washed 3-5 times with an appropriate amount of anhydrous methanol, and dried at 80°C overnight.
[0052] (2) Synthesis and optimization of Thy@ZIF-8 nanoparticles: 2.4 g of zinc nitrate hexahydrate and 10 mg, 20 mg, 30 mg, 40 mg, and 50 mg of thymol (Thymol, Thy) were fully dissolved in 30 mL of anhydrous methanol as liquid A, and 6.9 g of 2-methylimidazole was fully dissolved in 30 mL of anhydrous methanol as liquid B. The mixture was gently stirred at room temperature for 2 h. Liquid A was added to liquid B while stirring and mixed evenly. After reacting for 24 h, a white suspension was obtained. The white precipitate was collected by centrifugation at 9000 rpm / min for 5 min, washed 3-5 times with an appropriate amount of anhydrous methanol, and dried at 80°C overnight.
[0053] The encapsulation efficiency of nanoparticles with different Thy addition amounts was tested. The results are as follows Figure 2 As shown, Thy@ZIF-8 nanoparticles containing 30 mg Thy with a higher encapsulation efficiency were subsequently selected, and the content of ZIF-8 nanoparticles was 100 mg.
[0054] Preparation Example 2
[0055] Synthesis and optimization of chitosan-proanthocyanidin (CS-PA) conjugate: CS was completely dissolved in 100 mL of acetic acid solution (2%, v / v) to a final concentration of 1% (w / v), and then 2 mL of hydrogen peroxide solution (1.0 mol / L) containing 0.108 g of ascorbic acid was added to the CS solution. After reacting for 30 min, PA was added to the CS solution according to the molar ratio of PA:CS=0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, and 0.10:1. The reaction was carried out at room temperature for 24 h, and the pH was adjusted to 7.0 with NaOH solution (1 mol / L). The precipitate was collected by centrifugation at 8000 rpm / min for 5 min, washed three times with distilled water, and freeze-dried to obtain the product.
[0056] The PA content of the conjugates with different PA addition amounts was determined, such as Figure 3As shown, it can be seen that the PA content of the conjugate with PA:CS=0.04:1 is the highest, and increasing the amount of PA will not increase the PA content in the conjugate. The amount of PA added is determined to be PA:CS=0.04:1.
[0057] Comparative Preparation Example
[0058] (1) Preparation of CS film: CS was dissolved in 50 mL of 1% glacial acetic acid and rapidly stirred at room temperature for 30 min to prepare a CS solution. After stirring, glycerol was added as a plasticizer to obtain a CS film-forming solution. The solution was poured into a plastic plate (14 cm × 9 cm × 2.5 cm) and dried to successfully prepare a CS film.
[0059] (2) Preparation of CS-PA membrane:
[0060] CS-PA was dissolved in 50 mL of distilled water and rapidly stirred at room temperature for 30 min to prepare a CS-PA solution. After stirring, glycerol was added as a plasticizer to obtain a CS-PA film-forming solution. The solution was poured into a plastic plate (14 cm × 9 cm × 2.5 cm) and dried to successfully prepare a CS-PA film.
[0061] (3) Preparation of CS-PA / Thy membrane
[0062] CS-PA was dissolved in 50 mL of distilled water and stirred rapidly at room temperature for 30 min to prepare a CS-PA solution. Thy was dissolved in 50 mL of distilled water and stirred rapidly at room temperature to obtain a CS-PA solution. The CS-PA solution and the Thy solution were mixed and stirred. After stirring, glycerol was added as a plasticizer to obtain a CS-PA / Thy film-forming solution. The solution was poured into a plastic plate (14 cm×9 cm×2.5 cm) and dried to successfully prepare a CS-PA / Thy film.
[0063] Example 1
[0064] This example is used to illustrate the preparation method of the self-assembled Thy@ZIF-8 nanoparticles of the present invention.
[0065] 1) Preparation of Thy@ZIF-8 nanoparticles: 6.9 g 2-methylimidazole and 30 mg thymol were weighed and dissolved in 30 mL anhydrous methanol. After ultrasonic treatment, the mixture was mixed with 2.4 g Zn(NO3)2·6H2O dissolved in 30 mL methanol solution and magnetically stirred at room temperature for 24 h and then centrifuged at 9000 rpm / min for 5 min to obtain a white precipitate. The mixture was washed with an appropriate amount of anhydrous methanol for 3-5 times and vacuum dried at 80°C overnight to obtain Thy@ZIF-8 nanoparticles.
[0066] 2) Characterization of Thy@ZIF-8 nanoparticles: Figure 4 As shown in Figure 2, the morphology of ZIF-8 nanoparticles is a classic rhombic dodecahedron structure, and the particle size is about 116.67nm. Thy@ZIF-8 nanoparticles show a similar morphology to ZIF-8, and their average diameter is slightly increased to about 141.77nm ( Figure 4 (a)-(d)). In addition, the Zeta potential of Thy@ZIF-8 nanoparticles after encapsulation changed ( Figure 4 (e)). XRD and FT-IR spectra further confirmed the successful synthesis of Thy@ZIF-8 nanoparticles ( Figure 4 (f)-(g)).
[0067] 3) Performance determination of Thy@ZIF-8 nanoparticles: Figure 4 As shown in (h), the TG curve shows that Thy completely evaporates at around 160.1°C, which is attributed to the unique thermal instability and volatility of Thy. The first degradation of ZIF-8 occurs at 210°C with a weight loss of 2.06%, which can be attributed to the low content of water molecules in ZIF-8 nanoparticles. In addition, the ZIF-8 framework structure degrades at 590°C with a weight loss of approximately 12.52%. It is worth noting that Thy@ZIF-8 exhibits two degradation stages, with the highest temperatures at 195.6°C and 614.8°C, respectively. The first stage may be due to the degradation of tightly bound Thy in Thy@ZIF-8, and the second stage is due to the degradation of the ZIF-8 framework. Thermogravimetric analysis further confirmed that Thy was successfully encapsulated in ZIF-8, and Thy@ZIF-8 exhibited excellent thermal stability due to the protective effect of the ZIF-8 framework.
[0068] Example 2
[0069] This example is used to illustrate the preparation method of the self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film based on Thy@ZIF-8 nanoparticles of the present invention.
[0070] 1) Preparation of composite film: CS was dissolved in 50 mL of 1% glacial acetic acid, and the CS solution was prepared by rapid stirring at room temperature for 30 min. After stirring, glycerol was added as a plasticizer to obtain a CS film-forming solution. Further, CS-PA and Thy@ZIF-8 were dissolved in 30 mL and 20 mL of distilled water, respectively, to prepare CS-PA and Thy@ZIF-8 dispersions, which were rapidly stirred at room temperature for 30 min. The dispersions were added to the CS solution and blended. After reacting for 3 h, 100 mL of the blended solution was poured into a plastic plate (14 cm × 9 cm × 2.5 cm). After drying, the CS-PA / Thy@ZIF-8 composite film was successfully prepared. Among them, the content of self-assembled Thy@ZIF-8 nanoparticles was 30% by weight; the content of proanthocyanidins was 20% by weight.
[0071] 2) Characterization of composite films: Figure 5 As shown in (a), the SEM images of each group of films show that the surface of the CS film is smooth and uniform, without cracks or holes, indicating that a dense structure has been formed. After adding PA and Thy to CS, the uneven surface of the film gradually appeared, and the surface appeared uneven and small holes. This is due to the phase separation caused by the insolubility of Thy in water. At the same time, the roughness of the film increased significantly. After Thy was encapsulated in ZIF-8, the roughness was significantly improved. In addition, the SEM image of the CS-PA / Thy@ZIF-8 composite film shows that the Thy@ZIF-8 nanoparticles are uniformly dispersed in the CS-PA matrix, and there is no phase separation or aggregation, indicating that Thy@ZIF-8 has good compatibility with the film-forming matrix.
[0072] It can be seen from the XRD and FT-IR spectra that the crystal form of ZIF-8 nanoparticles has not changed, and hydrogen bonds and electrostatic interactions may be formed between ZIF-8 and Thy in Thy@ZIF-8 nanoparticles ( Figure 5 (c), (d)).
[0073] AFM images ( Figure 5 (b) shows that the CS film is smooth and uniform without cracks or pores, indicating a dense structure. However, after the addition of PA and Thy, protrusions and small holes appeared on the surface, which may be due to the phase separation caused by the insolubility of Thy, resulting in a significant increase in surface roughness (Ra increased from 1.03 to 25.4). Encapsulating Thy in ZIF-8 can improve the surface roughness and reduce Ra to 2.79.
[0074] XPS analysis further confirmed the above findings, such as Figure 5(c), the shifts of C1s and Zn 2p spectra indicate the existence of weak hydrogen bonds and coordination bonds between CS, PA, Thy and ZIF-8. Specifically, when Zn 2p binds to CS-PA, the Zn 2p peaks at 1043.86eV and 1020.77eV shift, indicating that Zn interacts with the reactive groups of CS and PA, and the N1s peak at 401.18eV indicates the existence of Zn-N coordination bonds between Thy@ZIF-8 and CS. The excellent interfacial compatibility generated by hydrogen bonding and coordination interactions is expected to improve the gas barrier and mechanical properties of the composite film, making it an ideal candidate for food packaging applications.
[0075] Example 3
[0076] This example is used to illustrate the performance measurement of the self-enhanced multifunctional fresh-keeping CS-PA / Thy@ZIF-8 composite film according to the present invention and the fresh-keeping effect test of post-harvest fruits under the actual storage environment.
[0077] (1) Physical properties of composite films: The physical properties of CS-PA / Thy@ZIF-8 composite films were analyzed by stretchability and light transmittance. Figure 6 As shown in (a), the stress-strain curve shows that the tensile strength of the CS film is low. With the addition of Thy@ZIF-8, the tensile strength of the CS-PA / Thy@ZIF-8 film is improved, which is attributed to the self-reinforcement effect of Thy@ZIF-8 and the interfacial interaction between Thy@ZIF-8 and the CS-PA matrix, thereby improving the mechanical properties of the composite film. Figure 6 As shown in (b), the transmission spectra of different films show that the pure CS film is transparent and has a high UV transmittance, while the transparency of the composite film gradually decreases and the UV light blocking ability increases. When PA is added to the CS matrix, the UV transmittance of the CS-PA film is significantly reduced because PA itself is red. In addition, after doping Thy@ZIF-8 nanoparticles into CS-PA, the transmittance in the ultraviolet region is significantly reduced, which may be due to the low transmittance and scattering effect of Thy@ZIF-8 nanoparticles. Figure 6 As can be seen from (c), the CS-PA / Thy@ZIF-8 composite film has a higher water contact angle, indicating that the surface hydrophobicity of the material is good. Further, the controlled release behavior of the free CS-PA / Thy film and the CS-PA / Thy@ZIF-8 film under acidic and neutral conditions was evaluated using pH 3, 5 and PBS solutions. Figure 6(d) It can be observed that the release of Thy from all membranes follows a similar two-step biphasic process. In the first 10 hours, the CS-PA / Thy membrane experienced a significant Thy burst release process, which was mainly caused by the swelling of surface-exposed Thy and the CS membrane matrix. The real-time release at 10 h reached more than 65% of the cumulative release; benefiting from the inherent binding effect of the CS membrane, the second stage transformed into a slow release until an isochoric release was reached. Compared with the CS-PA / Thy membrane, the CS-PA / Thy@ZIF-8 membrane exhibited a significantly slower Thy release process throughout the test interval, and the real-time release rate at 140 h was as low as 60%.
[0078] (2) Antioxidant activity of composite films: DPPH solution and ABTS solution were used to determine the antioxidant activity of CS films, CS-PA films, CS-PA / Thy films, and CS-PA / Thy@ZIF-8 composite films. Different groups of films were added with 95% ethanol solution containing 0.35 mM DPPH, incubated for 1 hour in the dark, and then the absorbance at 517 nm was read using a UV-visible spectrophotometer. ABTS was measured by incubating with different groups of films in the dark for 20 minutes, and then reading the absorbance at 734 nm. The results showed that ( Figure 6 (e)), the antioxidant capacity of CS film is poor, and its scavenging rate of DPPH radicals and ABTS+ always remains at a low level. On the contrary, different components added to the composite film will improve its antioxidant activity to varying degrees. Among them, CS-PA / Thy film and CS-PA / Thy@ZIF-8 composite film have the highest scavenging rates of DPPH radicals and ABTS+, indicating that the enhancement of the antioxidant capacity of the composite film is directly related to the addition of PA and Thy, especially the hydrogen atom donor of the phenolic hydroxyl group in Thy is crucial for the scavenging of DPPH radicals. At the same time, the single electron transfer between Thy and ABTS+ is the main reason for the scavenging of ABTS+.
[0079] (3) Antibacterial activity of composite films: Staphylococcus aureus and Escherichia coli are the most common Gram-positive and Gram-negative foodborne pathogens in food hygiene. The antibacterial activity of PE cling film, CS film, CS-PA film, CS-PA / Thy film and CS-PA / Thy@ZIF-8 composite film was tested using these two bacteria as representatives. Figure 7The antibacterial ability of CS-PA / Thy@ZIF-8 composite film is shown. (a) and (b) are the growth curves of PE cling film, CS film, CS-PA film, CS-PA / Thy film, CS-PA / Thy@ZIF-8 composite film co-cultured with Staphylococcus aureus and Escherichia coli; (c) Bacterial dead / alive staining images after co-culture of different films with Staphylococcus aureus and Escherichia coli, where green fluorescence represents live bacterial cells and red fluorescence represents dead bacterial cells. It can be seen that most of the bacteria in the control group are alive, and the four experimental groups of CS, CS-PA, CS-PA / Thy, and CS-PA / Thy@ZIF-8 all cause bacterial death, and the composite film has the most red fluorescence, representing the most dead bacterial cells. The overnight cultured bacterial solution (1×10 6 CFU / mL) were co-cultured with different films for 30 min, centrifuged at 8000 rpm / min for 5 min, and 100 μL of the supernatant was evenly spread on a TSB medium solid plate. Figure 7 As shown in (d), the results showed that compared with the control group of PE cling film, the number of bacteria on the plate showed a decreasing trend with the increase of film doping, among which there were almost no bacterial colonies on the CS-PA / Thy@ZIF-8 composite film plate, indicating that almost all the bacteria in this group were killed, which was attributed to the synergistic antibacterial effect of CS-PA matrix and Thy@ZIF-8 nanoparticles.
[0080] (4) Biocompatibility of composite films: The cytotoxicity of PE cling film, CS film, CS-PA film, CS-PA / Thy film and CS-PA / Thy@ZIF-8 composite film was evaluated using sheep red blood cell hemolysis test and mouse fibroblast cell line L-929 cell proliferation test. Red blood cells separated from fresh sheep whole blood were incubated with different film solutions at 37°C for 30 minutes, centrifuged at 3000 rpm for 5 minutes, and the supernatant was collected. The absorbance at 540 nm was read using a UV-visible spectrophotometer. The cell proliferation experiment used a CCK-8 kit to measure the absorbance at 450 nm of L-929 cells after incubation with different film solutions and CS-PA / Thy@ZIF-8 composite films at different concentrations for 24 hours. Figure 8 As shown in (a), (b) and (c), the results show that when L-929 cells are co-incubated with high concentrations of different film solutions and different concentrations of CS-PA / Thy@ZIF-8 composite films, the viability of L-929 cells remains above 90%, and there is no obvious hemolysis of sheep red blood cells, reflecting that the CS-PA / Thy@ZIF-8 composite film has good biocompatibility.
[0081] (5) Degradability of composite film:
[0082] The composite film was cut into 9cm×9cm circles, and the PE film was used as the control group. They were buried in the soil at a depth of 8-10cm. The morphology of the composite film and the PE film was photographed at a fixed time point every day. Figure 8 As shown in (d), it can be seen that the CS-PA / Thy@ZIF-8 composite film has good degradation performance.
[0083] (6) Biosafety of composite films:
[0084] Peanut seeds were immersed in water for germination at room temperature. After germination, the peanut seedlings were transferred to a solution containing CS-PA / Thy@ZIF-8 film (concentration of 1 mg mL -1 ) were placed in a culture vessel at room temperature for further cultivation. As a control, another group of peanut seedlings were placed in a culture vessel containing only tap water for cultivation. Under the same experimental conditions, pictures of the growth appearance of peanut seedlings were taken at fixed time points on the 3rd, 6th, 10th, 15th and 18th days. The results are shown in Figure 8 As shown in (e), it can be seen that the CS-PA / Thy@ZIF-8 composite film did not affect the growth of peanut sprouts, and it has good biosafety.
[0085] (7) Post-harvest fruit preservation effect test: Freshly picked strawberries and cherry tomatoes of similar quality were used as experimental materials to study the preservation effects of PE cling film, CS film, CS-PA film, CS-PA / Thy film and CS-PA / Thy@ZIF-8 composite film. The storage temperature of strawberries was room temperature, and the storage temperature of cherry tomatoes was 4°C. The selected fruits were divided into 6 groups and stored in PE cling film, CS film, CS-PA film, CS-PA / Thy film and CS-PA / Thy@ZIF-8 composite film respectively. The control group was a control group without any preservation treatment. During the storage process, the physiological indicators of the fruits such as decay index, weight loss rate, hardness, pH and soluble solids were monitored and recorded in real time at the same time every day. At the same time, sensory evaluation was conducted around the five indicators of appearance, smell, color, liking and purchase desire. Each indicator was scored 10 points, with a total score of 50 points. A total of 50 volunteers participated.
[0086] The test results of strawberry are as follows Fig. 9 As shown, specifically, Fig. 9 As shown in (a)-(h), the results show that the weight loss rate, TSS, TA and Vc of the CS-PA / Thy@ZIF-8 composite film are maintained at a better level than those of strawberries stored under other films, indicating that the composite film has better barrier properties for O2, CO2 and water vapor than single component films, further confirming that hydrogen bonds and Zn 2+The interaction of coordination bonds and the synergistic antibacterial and antioxidant effects of PA and Thy realize the self-enhancement of the fresh-keeping performance of the composite film. Fig. 9 As shown in (i) and (j), it can be seen that on the second and sixth days of storage, the CS-PA / Thy@ZIF-8 composite film group had the highest scores in all sensory evaluations, especially on the sixth day, when all indicators exceeded those of other experimental groups, indicating that with the increase of storage time, the preservation effect of the CS-PA / Thy@ZIF-8 composite film group became more prominent.
[0087] The test results of cherry tomatoes preservation are as follows Fig.10 As shown, since the cherry tomatoes were stored at 4°C, there was no obvious decay in each group, but it can still be seen that the cherry tomatoes in the CS-PA / Thy@ZIF-8 composite film group were the freshest, indicating that the CS-PA / Thy@ZIF-8 composite film had the best preservation effect.
[0088] Fig.11 The indexes of cherry tomatoes stored in different groups of films at different storage times are shown. It can be seen that the weight loss rate, hardness, Vc content, TSS content, TA, MDA content, flavonoid content, total phenol content and CAT activity of CS-PA / Thy@ZIF-8 composite film are maintained at a better level compared with cherry tomatoes stored in other films.
[0089] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A self-assembled Thy@ZIF-8 nanoparticle, characterized in that: The self-assembled Thy@ZIF-8 nanoparticles are nanoparticles formed by encapsulating thymol Thy in a metal organic framework material ZIF-8.
2. The self-assembled Thy@ZIF-8 nanoparticles according to claim 1, characterized in that: The content of ZIF-8 in the self-assembled Thy@ZIF-8 nanoparticles is 70-85% by weight, and the content of Thy is 15-30% by weight.
3. The method for preparing the self-assembled Thy@ZIF-8 nanoparticles according to claim 1 or 2, characterized in that: The following steps are involved: 2-Methylimidazole and thymol were dissolved in a first organic solvent and then treated with ultrasound and Zn 2+ The precursor solutions were mixed evenly, stirred for reaction, and then centrifuged to obtain Thy@ZIF-8 nanoparticles.
4. The preparation method according to claim 3, characterized in that: The first organic solvent is anhydrous methanol; The Zn 2+ The precursor is Zn(NO3)2·6H2O; 2-Methylimidazole and Zn 2+ The molar ratio of the precursor is 2 to 12:1; The mass ratio of 2-methylimidazole to thymol is 200-300:
1.
5. The preparation method according to claim 3, characterized in that: The stirring reaction conditions include: temperature of 10 to 30° C. and time of 16 to 36 hours. After the stirring reaction, the steps of washing and vacuum drying are also included.
6. A self-reinforced multifunctional fresh-keeping composite film, characterized in that: The film is based on chitosan, and at least part of the chitosan is grafted with proanthocyanidins. The film contains the self-assembled Thy@ZIF-8 nanoparticles according to claim 1 or 2.
7. The self-reinforced multifunctional fresh-keeping composite film according to claim 6, characterized in that: The content of self-assembled Thy@ZIF-8 nanoparticles in the self-reinforced multifunctional fresh-keeping composite film is 25-35% by weight; and the content of proanthocyanidins is 15-25% by weight.
8. The method for preparing the self-reinforced multifunctional fresh-keeping composite film according to claim 6 or 7, comprising the following steps: Chitosan-proanthocyanidin conjugate CS-PA and Thy@ZIF-8 nanoparticles were dissolved in distilled water respectively and stirred rapidly at room temperature to obtain CS-PA dispersion and Thy@ZIF-8 dispersion. CS-PA dispersion and Thy@ZIF-8 dispersion were added into chitosan film-forming solution for blending reaction. The blended solution after reaction was film-formed and dried to obtain CS-PA / Thy@ZIF-8 composite film.
9. The preparation method according to claim 8, wherein: Stir quickly until the solution is uniform and free of particles; The preparation method of chitosan-proanthocyanidin conjugate CS-PA comprises: adding a hydrogen peroxide solution containing ascorbic acid to an acetic acid solution of chitosan, reacting for a period of time, adding proanthocyanidin, reacting at room temperature, adjusting the reaction solution to neutral after the reaction, collecting the precipitate by centrifugation, washing, and freeze-drying to obtain the chitosan-proanthocyanidin conjugate CS-PA; The method for preparing the chitosan film-forming solution comprises: dissolving chitosan in glacial acetic acid to prepare a chitosan solution, and adding glycerol as a plasticizer to obtain the chitosan film-forming solution; The film-making method is as follows: pouring the blended solution onto a plastic plate.
10. Use of the self-assembled Thy@ZIF-8 nanoparticles according to claim 1 or 2, or the self-reinforced multifunctional fresh-keeping composite film according to claim 6 or 7 in post-harvest storage of fruits and vegetables.
Citation Information
Patent Citations
MOF-loaded procyanidine antibacterial membrane and preparation method thereof
CN110818955A
Preparation method and application of sustained and controlled release antibacterial chitosan-based composite membrane
CN113292753A
Preparation method of procyanidine-deep eutectic solvent-chitosan composite fresh-keeping film
CN117004095A